2014
DOI: 10.5306/wjco.v5.i3.272
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain following breast cancer diagnosis: Implication and proposed mechanisms

Abstract: Weight gain occurs in the majority of women following breast cancer treatment. An overview of studies describing weight gain amongst women treated with early to modern chemotherapy regimens is included. Populations at higher risk include women who are younger, closer to ideal body weight and who have been treated with chemotherapy. Weight gain ranges between 1 to 5 kg, and may be associated with change in body composition with gain in fat mass and loss in lean body mass. Women are unlikely to return to pre-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 68 publications
5
109
3
8
Order By: Relevance
“…Weight gain is a common and persistent problem in breast cancer patients, especially those who are younger, closer to ideal body weight and who have been treated with chemotherapy [15]. Several studies [16-18] have demonstrated that weight gain post-diagnosis increases the risk of all-cause mortality and recurrence, including a report from our study [19]; whereas other studies found no relation [20-22].…”
Section: Introductionmentioning
confidence: 55%
“…Weight gain is a common and persistent problem in breast cancer patients, especially those who are younger, closer to ideal body weight and who have been treated with chemotherapy [15]. Several studies [16-18] have demonstrated that weight gain post-diagnosis increases the risk of all-cause mortality and recurrence, including a report from our study [19]; whereas other studies found no relation [20-22].…”
Section: Introductionmentioning
confidence: 55%
“…Some described how they used less healthy 'comfort' foods as rewards in the context of challenging cancer diagnosis and treatment scenarios or that they were driven toward high sugar, high fat foods because flavour sensitivity was diminished. Despite these observations, overeating has been deemed an unlikely reason for weight gain in breast cancer populations in light of empirical data demonstrating total reductions in caloric intake in the first year following a breast cancer diagnosis (Makari-Judson et al 2014). …”
Section: Smell Structural Surgical Removal Of Structures Involved In mentioning
confidence: 99%
“…To date, most of the research pertaining to weight gain as a breast cancer treatment side effect has focused on weight changes during or following adjuvant chemotherapy [21,22]. By contrast, research pertaining to weight change during adjuvant endocrine treatment (ET) is very limited.…”
Section: Introductionmentioning
confidence: 99%